2012
DOI: 10.1016/j.ejca.2012.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of lung cancer in individuals with a family history of the disease: A pooled analysis from the International Lung Cancer Consortium

Abstract: Background and Methods Familial aggregation of lung cancer exists after accounting for cigarette smoking. However, the extent to which family history affects risk by smoking status, histology, relative type and ethnicity is not well described. This pooled analysis included 24 case-control studies in the International Lung Cancer Consortium. Each study collected age of onset/interview, gender, race/ethnicity, cigarette smoking, histology and first-degree family history of lung cancer. Data from 24,380 lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 64 publications
9
114
1
4
Order By: Relevance
“…59 (6) 57 (5) 58 (5) 65 (5) 61 (4) 59 (6) Current smokers at randomisation, % 55 76 61 55 65 63 Mean pack-years (± SD) 42 (19) 36 (13) 36 (18) 47 (25) 43 (18) …”
Section: European Lung Cancer Screening Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…59 (6) 57 (5) 58 (5) 65 (5) 61 (4) 59 (6) Current smokers at randomisation, % 55 76 61 55 65 63 Mean pack-years (± SD) 42 (19) 36 (13) 36 (18) 47 (25) 43 (18) …”
Section: European Lung Cancer Screening Trialsmentioning
confidence: 99%
“…For ribonucleic acid (RNA), later samples of buccal (6) and nasal (7) scrapes, the nasal samples were superior in all measurements. Whereas 6 of 10 nasal samples gave Qubit concentrations of > 10 ng/µl (range 15-120 ng/µl) and RNA integrity number (RIN) values of 6.1-7.8, only 4 of 10 buccal samples gave similar amounts (range 15-69 ng/µl) but with lower RIN values of 0-5.9.…”
Section: What Should I Do Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to welding fumes at work place (Mannetje et al, 2012), cooking fumes (Yin et al, 2013), sedentary living (Yang et al, 2003), family history (Cote et al, 2012), exposure to wood dust (Bhatti et al, 2011), alcoholism (Bagnardi et al, 2010) and asbestos exposure (Markowitz et al, 2013) has also been reported in Caucasian, American, African and Asian populations as positive risk factors of lung cancer. But high OR value of 2.5 in Pakistani population for welding fumes in present study is higher than any other parts of the world.…”
Section: Causative Factorsmentioning
confidence: 99%
“…Lung cancer is becoming the worldwide top male cancer type with highest morbidity and mortality (Coté et al, 2012). About 80-85% lung cancer cases are none-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%